Implementation of the Attorney General Regulation of Republic Indonesia No.15 of 2020 on Discontinuation of Prosecution Based on Restorative Justice at the High Prosecutor's Office - Yoan Barbara Runtunuwu,; Fatimah Hs, (Technium Social Sciences Journal, 2023)
Implementation of the Attorney General of the Republic of Indonesia's Regulation No. 15 of 2020 on Prosecution Termination Based on Restorative Justice at the High Prosecutor's Office has positively impacted the resolution of criminal cases in Indonesia. Restorative justice provides a more effective solution in resolving criminal cases by prioritizing restorative and rehabilitative efforts rather than relying on punishment as the only solution. Case resolution in this way benefits all parties, including victims, perpetrators, and society as a whole. However, there are certain difficulties in putting restorative justice into practice, such as a lack of public understanding and awareness of the concept, a lack of qualified human resources to implement restorative justice, and a lack of support from security forces and the government. Therefore, efforts are needed to increase public understanding and awareness of the restorative justice concepts, improve the qualifications of human resources involved in implementing restorative justice, and gain support from security forces and the government so that restorative justice can be implemented more widely and effectively in Indonesia.